Simphony: A Next Generation Simulation Modelling Environment for the Construction Domain - AbouRizk, S.; Hague, S.; Ekyalimpa, R.; Newstead, S. (Journal of Simulation, 2016)
This paper discusses Simphony simulation system in the public domain. Simphony has unique features suitable for solving construction engineering problems. This discussion commences by presenting an overview of simulation, the different simulation methods, and the tools that support these methods. Simphony is then presented as an environment that supports building simulation solutions based on discrete event and continuous simulation. Key features that make Simphony unique are highlighted, with a focus on the ability of the environment to build special purpose simulation tools, an extensible API, an integrated calendar that facilitates building complex models sensitive to ‘date and real time’ information, data connectivity, and others. A practical special purpose simulator developed using Simphony used in a real life application is presented to demonstrate the use of some of these features.
Keywords: Simphony; extensible API; calendars; simulation methods